ANALISIS INOVASI PELAYANAN DI KEPOLISIAN DAERAH JAWA TENGAH (STUDI KASUS SMILE POLICE) - Nina Wahyuni; Maesaroh Maesaroh (Journal of Public Policy and Management Review, 2018)
The condition of society today have increased where society are more courageous to express their aspirations, needs and demands to government toward better public service delivery. As an effort to improve the quality of public services, the government has taken various ways continuously for improvement of public services in order to make first-rate realization of public services. One effort to improve the quality of public services is to do public service innovation. As an effort to improve the public service, Kepolisian Daerah Jawa Tengah launched an innovation called Smile Police. The writer uses attributes of innovation theory from Rogers and the theory of innovative driving and inhibiting factors in public sector from Clark and Albury to analyze how Smile Police's innovation works. The results showed that the implementation of Smile Police innovation has not only relative advantage, compabillity, triabillity and observabillity but also complexity. The driving factors of Smile Police's innovation are political push, economic pressure and increased efficiency and pressure to improve services, while the inhibiting factors are the excessive dependence on high performer, technology exists but inihibited by cultural and organizational barriers, and no rewards or incentives. The writer suggests to held sustainable socialization with the right target, recruit outsourced employees with expertise in IT, build cooperation with new partners and give awards or incentives to the members represented Smile Police.